Pengembangan Media Flashcard Bermuatan Kuliner Sasak pada Mata Pelajaran Bahasa Indonesia Materi Menulis Teks Deskriptif Siswa Kelas IV SDN 1 Aikmel - Bq. Siska Apriani; Asrin; Moh. Irawan Zain; Syarifuddin (Mataram University, 2026)
This research was motivated by the low descriptive text writing skills among fourth-grade students at SDN 1 Aikmel due to monotonous learning methods and a lack of visual media. Initial observations showed that students struggled to select appropriate vocabulary, arrange coherent sentences, and develop ideas into complete descriptive texts, while teachers relied mainly on lecture-based instruction and student worksheets (LKS). This study aimed to describe the prototype, validity, practicality, and effectiveness of flashcard media embedded with Sasak culinary themes. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved fourth-grade students at SDN 1 Aikmel as subjects. Data were collected through interviews, questionnaires, tests (pretest-posttest), and documentation, and then analyzed using descriptive quantitative methods. The results showed that the developed flashcard media was highly valid, scoring 92% from instrument experts and 83% from media experts. The media was also deemed practical, achieving response rates of 85.45% from students and 80% from teachers. Furthermore, the media proved effective in improving students' writing skills, as indicated by an increase in test scores from a pretest range of 40–72 to a posttest range of 76–96, with an N-gain score of 0.5–0.8 (moderate to high category). It can be concluded that the flashcard media embedded with Sasak culinary themes is valid, practical, and effective in enhancing descriptive text writing skills while supporting the preservation of local wisdom through contextual learning.